The technical and economic rationale embedding downhole compensators in the oil field - V. A. Kopyrin (Омский научный вестник)
The purpose of the article is a discussion of economic considerations of the feasibility of incorporating downhole compensator of reactive power in oil fields with active high-debit wells. Actual and calculated parameters of power consumption of electric centrifugal pumps under consideration are given before and after compensation of reactive power inside well. It has been found that the positive energy effect of the downhole compensators varies from 3,2 to 8,2 % by reducing the loss in the electrical engineering complex of the plants. The positive economic effect varies from 174,3 to 284,1 thousand rubles for the oil wells under consideration.